(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics and to evaluate the outcomes of monopolar transurethral resection of the prostate (TURP) in the treatment of benign prostatic hyperplasia (BPH). Subjects and Methods: A study was conducted on 108 patients diagnosed with BPH who underwent TURP at Son La General Hospital from January 2024 to October 2025. Results: The mean age was 71.99 ± 9.79 years (range: 56–95). The mean preoperative International Prostate Symptom Score (IPSS) was 25.26 ± 6.26, and the mean preoperative quality of life (QoL) score was 4.92 ± 1.02. The mean preoperative prostate volume was 50.50 ± 17.23 gram. Post-catheter removal complications included dysuria in 14.8% of patients, hematuria in 10.2%, urinary retention in 7.4%, and urinary incontinence in 5.6%. The mean IPSS improved to 6.25 ± 1.98 postoperatively and 3.69 ± 1.73 at 3 months. The mean QoL score improved to 1.74 ± 0.81 postoperatively and 0.89 ± 0.48 at 3 months. The mean prostate volume decreased to 18.89 ± 6.64 gram postoperatively and 17.67 ± 6.24 gram at 3 months. Treatment outcomes were classified as very good (86.4%), good (9.3%), fair (4.3%), and poor (0%). Conclusion: Transurethral resection of the prostate is a safe and effective surgical method for the treatment of benign prostatic hyperplasia, significantly improving patients’ quality of life.